The beneficial effect of traditional Japanese herbal (Kampo) medicine, Hochu‐ekki‐to (Bu‐Zhong‐Yi‐Qi‐Tang), for patients with chronic wounds refractory to conventional therapies: A prospective, randomized trial. Issue 6 (9th August 2019) - Akita, Shinsuke; Namiki, Takao; Kawasaki, Yohei; Rikihisa, Naoaki; Ogata, Hideyuki; Tokumoto, Hideki; Tezuka, Takafumi; Kubota, Yoshitaka; Kuriyama, Motone; Nakamura, Michimi; Mitsukawa, Nobuyuki
ABSTRACT: Hochu‐ekki‐to (HET) is a traditional Japanese herbal (Kampo) medicine for the treatment of severe weakness, loss of appetite, and indigestion in elderly patients and for the prevention of opportunistic infections. The impact of HET on patients with chronic wounds refractory to conventional therapies was investigated in a prospective, randomized trial, including 18 patients divided into medication (7.5 g oral HET per day, n = 9) and control ( n = 9) groups. Wound healing during the 12‐week study period was scored based on depth, exudate, size, inflammation/infection, granulation tissue, necrotic tissue, and pocket size. At 12 weeks, wound healing progressed in all nine patients in the medication group, whereas wound healing progressed in only three patients in the control group (significant difference, p  < 0.01; relative risk: 3.00). In the medication group, the total score decreased significantly at 8 weeks and later. To the best of our knowledge, this study was the first to show that HET promoted the healing of chronic wounds resistant to conventional treatments. HET may be a choice as an adjunctive therapy for chronic wounds, particularly for patients with malnutrition. This trial was registered with the University Hospital Medical Information Network Clinical Trials Registry (UMIN000031620).